Identification of Two Depolymerases From Phage IME205 and Their Antivirulent Functions on K47 Capsule of Klebsiella pneumoniae - Liu, Yannan; Leung, Sharon Shui Yee; Huang, Yong; Guo, Yatao; Jiang, Ning; Li, Puyuan; Chen, Jichao; Wang, Rentao; Bai, Changqing; Mi, Zhiqiang; Gao, Zhancheng (Frontiers in Microbiology, 2020)
Carbapenem-resistant Klebsiella pneumoniae (CRKP) pose a significant threat to global public health. In present research, a total of 80 CRKP strains belonging to ST11 were collected with 70% (56 of 80 isolates) expressing a K47 capsular type. Thus, it is significant to prevent and control infections caused by these bacteria. Capsule depolymerases could degrade bacterial surface polysaccharides to reduce their virulence and expose bacteria to host immune attack. Previous studies have demonstrated the potential of phage-encoded depolymerases as antivirulent agents in treating CRKP infections in vitro and in vivo. Here, two capsule depolymerases (Dpo42 and Dpo43) derived from phage IME205 were expressed and characterized. Although both depolymerases act on strains with a capsular serotype K47, they are active against different subsets of strains, indicating the subtle differences in capsule composition exist within this serotype. The host range of phage IME205 matched to the sum of specificity range of Dpo42 and Dpo43. These two enzymes maintained stable activity in a relatively broad range of pH levels (pH 5.0-8.0 for Dpo42 and pH 4.0-8.0 for Dpo43) and temperatures (20-70 °C). Besides, both Dpo42 and Dpo43 could make host bacteria fully susceptible to the killing effect of serum complement and display no hemolytic activity to erythrocytes. In summary, capsule depolymerases are promising antivirulent agents to combat CRKP infections.